Perfil clínico-epidemiológico dos pacientes portadores de anomalias da diferenciação sexual atendidos no ambulatório de endocrinologia pediátrica do hospital Fundação Santa Casa de Misericórdia do Pará, no período de agosto de 2001 a outubro de 2010. - CHARONE, Daniel Magno (2023)
The Disorders of Sex Development are diseases that attend with genital and/or gonads alterations that can damage the child’s psychosocial integrity; they should be early investigated in any suspicious of atypical genitalia to define a proper clinical and surgical management. OBJECTIVES: the present study tried to demonstrate the epidemiological and clinical profile of the patients that have disorders of sex development and were consulted in Pediatrics Endocrinology Clinic of Hospital Fundação Santa Casa de Misericórdia do Pará, between August 2001 and October 2010. METODOLOGY: it was made an observational, descriptive, transversal study of prevalence using 157 medical records, but just 132 fits in inclusion and exclusion criteria, so was collected information about identification, familiar and personal history, clinical suspicious, physical examination, diagnostics methods, treatment options and follow-ups. All the data was stored, analyzed, coded and compiled trough Microsoft Excel® 2003, Microsoft Word® 2003, Epi Info 3.5.2 and BioEstat 5.0, so the tablets and graphics could be made and the central tendency measures and dispersion measures could be obtained, besides parametric tests with level of significance (values equal or minor than 0.05 reject the nullity hypothesis). RESULTS: 53.8% of the patients were coming from Pará State’s interior; 48.5% were registered like man, otherwise the non registered patients were diagnosed earlier (p<0.05); 16.7% had atypical genital history in family, 23.5% had neonatal death or abortion positive history and 7.6% had consanguinity parents; 75.8% were born in Hospital; the first suspicious was made in 42.4% newborns, 54.5% by pediatricians, with information that when this suspicious was made by doctors, the diagnosis was earlier (p<0.05); the first consult occurred in 32.6% infants; the Prader classification wasn’t referred in 84.8% of the cases; the Tanner staging was considered prepubescent in 74.2%; the clinical findings were, predominantly, hypospadia (n=43), cryptorchidism (n=41) and clitorimegaly (n=27); 68.9% of the diagnosis occurred at Pediatrics Endocrinology Clinic, with 36.2% infants; 100% of the patients done karyotype exam, being the 46,XY the most frequent with 42.4% followed by 46,XX with 23.5%; 24.2% realized histological examinations; 22.7% had congenital adrenal hyperplasia and 16.7% had etiological diagnosis of Turner Syndrome; 31.9% started the treatment in preschoolers; 51.3% started the treatment with less than three months from the etiological diagnosis; 34.1% did just clinical treatment, against 18.9% did just surgical treatment; there was 5.3% of the patients that needed to correct the creation sex; 65.2% were in psychological care; 28.8% were doing irregular follow-ups, 37.1% abandoned the Clinic, which 30.6% returned to Service. CONCLUSION: the Pediatrics Endocrinology Clinic Service is essential for the management of the disorders of sex development. Otherwise the obtained results were very close to what was verified in the literature, it’s observed that there is shortage information about clinical and epidemiological profile of those patients, with plenty of limitation to care protocol, exposing that is need to upgrade the medical education for an easy recognizing and management against an atypical genitalia case, so the impacts in psychosocial life will be reduced.